Genitourinary syndrome of menopause exploring the history, updates and treatment - Elfaki, Sara H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The biological factors and physiological functions fundamental to the female anatomy delineate the complexity of reproductive phenomenon in this population. When women experience menopausal transition, genital, sexual, and urinary signs and symptoms materialize often. These longstanding signs and symptoms, presently referred to as the genitourinary syndrome (GUS) of menopause, a relatively new term, impact their quality of life and sexual health with the emergence of vulvovaginal and urogenital atrophy, typical of irritation, soreness, dryness, dyspareunia, and itching. Despite its prevalence, GUS of menopause often goes unreported due to embarrassment, leading to underdiagnoses, diminished intervention, and under-treatment. Moreover, the rising life expectancy is also emerging as a contributing factor to the increasing prevalence of GUS of menopause, directly affecting women’s health. While there are notable awareness, education, and healthcare frameworks in place aimed at addressing the unique needs of menopausal women, there is a need to explore further GUS’ prevalence, pathophysiology, risk factors, clinical features, diagnosis, and treatment to understand, diagnose, and effectively manage this condition.